2016
DOI: 10.1186/s13039-016-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

First molecular-cytogenetic characterization of Fanconi anemia fragile sites in primary lymphocytes of FA-D2 patients in different stages of the disease

Abstract: BackgroundFanconi anemia (FA) is a chromosomal instability syndrome characterized by increased frequency of chromosomal breakages, chromosomal radial figures and accelerated telomere shortening. In this work we performed detailed molecular-cytogenetic characterization of breakpoints in primary lymphocytes of FA-D2 patients in different stages of the disease using fluorescent in situ hybridization.ResultsWe found that chromosomal breakpoints co-localize on the molecular level with common fragile sites, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Knies and colleagues (KNIES et al, 2012) also pointed out that single heterozygous mutation in one FA gene may be accompanied by the heterozygous mutation in other FA genes and lead to the disease. Our previous detailed molecular-cytogenetic investigation of these patients showed that cases 1 and 2 in which 7 and 8 variants were found, respectively, developed, at the time of sampling, severe BMF, had shorter telomeres, more telomere fusions and radial figures and different chromosomal breakage pattern compared to other FA-D2 patients (JOKSIC et al, 2012;FILIPOVIC et al, 2016). This is consistent with Chang's statement that great number of variants reflects the susceptibility of FA pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Knies and colleagues (KNIES et al, 2012) also pointed out that single heterozygous mutation in one FA gene may be accompanied by the heterozygous mutation in other FA genes and lead to the disease. Our previous detailed molecular-cytogenetic investigation of these patients showed that cases 1 and 2 in which 7 and 8 variants were found, respectively, developed, at the time of sampling, severe BMF, had shorter telomeres, more telomere fusions and radial figures and different chromosomal breakage pattern compared to other FA-D2 patients (JOKSIC et al, 2012;FILIPOVIC et al, 2016). This is consistent with Chang's statement that great number of variants reflects the susceptibility of FA pathway.…”
Section: Discussionsupporting
confidence: 88%
“…The FANC pathway is dysfunctional in individuals with Fanconi anemia (FA), a rare chromosome instability disorder characterized by bone marrow failure, predisposition to acute myeloid leukemia and epithelial cancers, and hypersensitivity to DNA interstrand crosslinks (ICLs) and endogenous aldehydes 16 18 . Chromosomal aberrations in FA patients occur preferentially at CFSs 19 21 . FANCD2, a key component of the FANC pathway, has been shown to relocalize to large genes encompassing CFSs after replication stress 22 , 23 and form foci at CFSs during mitosis, where it cooperates with the Bloom’s syndrome helicase (BLM) to prevent chromosomal abnormalities 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Slides were dehydrated with increasing concentrations of ethanol (70, 95, and 100 %), stained with 4′,6′-diamidino-2-phenylindole (DAPI)-containing Vectashield solution (Vector Laboratories Ltd, Peterborough, UK), and analysed under a Zeiss-Axioimager A1 microscope (Carl Zeiss, Jena, Germany), with the ISIS imaging software package (MetaSystems Hard & Software GmbH, Altlussheim, Germany). At least 200 complete metaphase spreads per sample were analysed, whereas the scoring criteria included determination of karyotype and indicators of chromosome damage (chromosome breaks, dicentric and ring chromosomes, acentric fragments, and radial figures) (18,19).…”
Section: Discussionmentioning
confidence: 99%